Is It Actionable? An Evaluation of the Rapid PCR-Based Blood Culture Identification Panel on the Management of Gram-Positive and Gram-Negative Blood Stream Infections. (11th December 2018) - Tseng, Andrew S; Kasule, Sabirah N; Rice, Felicia; Mi, Lanyu; Chan, Lynn; Seville, Maria T; Grys, Thomas E
Abstract: Background: There is growing interest in the use of rapid blood culture identification (BCID) in antimicrobial stewardship programs (ASPs). Although many studies have looked at its clinical and economic utility, its comparative utility in gram-positive and gram-negative blood stream infections (BSIs) has not been as well characterized. Methods: The study was a quasi-experimental retrospective study at the Mayo Clinic in Phoenix, Arizona. All adult patients with positive blood cultures before BCID implementation (June 2015 to December 2015) and after BCID implementation (June 2016 to December 2016) were included. The outcomes of interest included time to first appropriate antibiotic escalation, time to first appropriate antibiotic de-escalation, time to organism identification, length of stay, infectious diseases consultation, discharge disposition, and in-hospital mortality. Results: In total, 203 patients were included in this study. There was a significant difference in the time to organism identification between the pre- and post-BCID cohorts (27.1 hours vs 3.3 hours, P < .0001). BCID did not significantly reduce the time to first appropriate antimicrobial escalation or de-escalation for either gram-positive BSIs (GP-BSIs) or gram-negative BSIs (GN-BSIs). Providers were more likely to escalate antimicrobial therapy in GP-BSIs after gram stain and more likely to de-escalate therapy in GN-BSIs after susceptibilities. Although there were no significant differences in changes in antimicrobial therapy for organism identification by BCID vs traditional methods, more than one-quarter of providers (28.1%) made changes after organism identification. There were no differences in hospital length of stay or in-hospital mortality comparing pre- vs post-BCID. Conclusions: Although BCID significantly reduced the time to identification for both GP-BSIs and GN-BSIs, BCID did not reduce the time to first appropriate antimicrobial escalation and de-escalation.